Error analysis of dynamical models in epidemiology - G. P. Pokhariyal; A. J. Rodrigues (International Journal of Mathematics and Mathematical Sciences)
In this paper we conduct the error analysis of two models used to simulate the disease profiles in plant pathogen epidemics. The role of the various model parameters is discussed in relation to accuracy